Distribution of Glyphosate- and Thifensulfuron-Resistant Palmer Amaranth (Amaranthus palmeri) in North Carolina - Amy H. Poirier; Alan C. York; David L. Jordan; Aman Chandi; Wesley J. Everman; Jared R. Whitaker (International Journal of Agronomy)
Glyphosate resistance in Palmer amaranth was first confirmed in North Carolina in 2005. A survey that year indicated 17 and 18% of 290 populations sampled were resistant to glyphosate and thifensulfuron, respectively. During the fall of 2010, 274 predetermined sites in North Carolina were surveyed to determine distribution of Palmer amaranth and to determine if and where resistance to fomesafen, glufosinate, glyphosate, and thifensulfuron occurred. Palmer amaranth was present at 134 sites. When mortality for each biotype was compared to a known susceptible biotype for each herbicide within a rate, 93 and 36% of biotypes were controlled less by glyphosate (840 g ae ha−1) and thifensulfuron (70 g ai ha−1), respectively. This approach may have underestimated resistance for segregating populations due to lack of homogeneity of the herbicide resistance trait and its contribution to error variance. When mortality and visible control were combined, 98% and 97% of the populations were resistant to glyphosate and the ALS inhibitor thifensulfuron, respectively, and 95% of the populations expressed multiple resistance to both herbicides. This study confirms that Palmer amaranth is commonly found across the major row crop production regions of North Carolina and that resistance to glyphosate and ALS-inhibiting herbicides is nearly universal. No resistance to fomesafen or glufosinate was observed.